Validation of resilient and drought adapted forage options in three agroecological regions of Mali - Report 2023-2024 - Ba, Alassane; Coulibaly, Doubangolo; van der Hoek, Rein (2024)
This report presents the partial and preliminary results of the forage trials in Mali implemented in 2023 and 2024 by l’Instititut d’Economie Rurale (IER) as part of the CGIAR Research Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion (SAPLING). Multi-locational agronomic and farmer participatory evaluation of the performance of resilient and drought adapted cultivars and hybrids of Urochloa (Brachiaria) and Megathyrsus (Panicum) grasses identified best options for the different regions and livestock systems in the country. Validation at farmers’ fields increased awareness and provided information of the impact on animal productivity and environmental indicators. The performance these forages indicates that they can constitute an important additional feed source for ruminants in the Sudan agro-ecological zone, which face chronic forage deficits affecting their productivity.